MEMBANGUN CUSTOMER CARE SYSTEM BAGI PENGGUNA PRODUK HEWLETT-PACKARD BERBASIS WEB - Harsono, Andri; Lestari, Uning; Iswahyudi, Catur (Jurnal Script, 2015)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Notebook is no longer a luxury item anymore but itâs become being demands in the work place and even at school. So many vendors offers their notebook series that fit to their customer needs, and one of them is Hewlett-Packard. With so many customers it should be handled seriously to full fill their needs about their product. As an electronic with thousands or even millions of electrical component inside, the possibility of damage cannot be avoided. Therefore an expert system is need to be made for customer to help them handle some faulty components. This expert system that build based on forward chaining as inference machine and Depth-First Search as searching method is designed as part of vendor concern about their customer and itâs covered from purchasing where customer registered their product until their product become out of warranty. This web based system offers their customer so they can do error troubleshooting and download driver need for their product in this case is notebook. The damage that customer experienced is not always detected properly in this system because some faulty conditions needs an expert technician to handle it. For customer, expert system using is very helpful as damage possibility reference that may happened based on existing symptom.Â Keyword: customer, expert system, web